Pengaruh E-Service Quality dan E-Trust Terhadap Loyalitas Nasabah PT Bank Syariah Indonesia KCP Binjai dalam Perspektif Ekonomi Islam - Rio Herda Warda Sitepu; Elida Elfi Barus (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the influence of e-service quality and e-trust on customer loyalty at PT Bank Syariah Indonesia (BSI) KCP Binjai through the lens of Islamic Economics. The research background is triggered by the dynamics of Islamic banking digitalization and the cyber system disruption in May 2023 that tested the resilience of customer trust. The research method used is quantitative with an associative approach. Data were collected via questionnaires from 100 active BSI KCP Binjai customers selected using purposive sampling. Data analysis was performed with multiple linear regression and classical assumption tests. The results indicate that e-service quality and e-trust have a positive and significant effect on customer loyalty, both partially and simultaneously. In an Islamic Economics perspective, digital service quality is an embodiment of ihsan and itqan, while trust is the implementation of amanah values. The study concludes that technological infrastructure stability and moral integrity are vital for maintaining customer loyalty in the digital era.